Analysis Of The Implementation Of Managerial Supervision By Madrasah Supervisors - Wahyuni, Tri; WisikaPrajanti, Sucihatiningsih Dian; Widodo, Joko (Proceedings of International Conference on Science, Education, and Technology, 2025)
This study aims to analyze the implementation of managerial supervision by madrasah supervisors at the Madrasah Tsanawiyah (MTs) level, covering aspects of planning, implementation, evaluation, and follow-up. Managerial supervision serves as an essential instrument for enhancing the effectiveness of madrasah principals' leadership and the quality of educational governance. The research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation at several MTs under the supervision of supervisors in Kudus Regency. The findings indicate that supervision planning has been systematically arranged, yet it lacks a strong foundation in the actual needs of the madrasahs. The implementation phase tends to emphasize administrative aspects and has not fully developed strategic coaching functions. While the evaluation process follows standard guidelines, it has not been optimized to support the professional development of madrasah principals. The follow-up actions on supervision results are not conducted consistently and show limited use of technology. Therefore, managerial supervision needs to be directed toward a more dialogical, quality-oriented, and data-driven coaching process that leverages information technology.